Synaesthesia is linked to more vivid and detailed content of autobiographical memories and less fading of childhood memories. Issue 6 (3rd July 2018) - Chin, Taylor; Ward, Jamie
ABSTRACT: People with synaesthesia have enhanced memory on a wide range of laboratory tests of episodic memory, but very little is known about their real-world memory. This study used a standard measure of autobiographical remembering (the Autobiographical Memory Questionnaire, AMQ) considering four constructs (Recollection, Belief, Impact and Rehearsal) and two time periods (recent memories from adulthood, remote memories from childhood). Synaesthetes reported more Recollection (e.g., sensory detail) and Belief (e.g., confidence) which interacted with time, such that remote memories are reported to be comparatively better preserved in synaesthetes. This cannot be explained by synaesthetes recalling more salient episodes (the groups did not differ in Impact). It suggests instead that childhood memories have a special status in synaesthesia that reflects the different neurodevelopmental trajectory of this group. With regards to Rehearsal, controls tended to report that more recent memories tend to resurface (i.e., adulthood > childhood), but the synaesthetes showed the opposite dissociation (i.e., childhood > adulthood).